OP02 Grip strength across the life course: normative data from twelve British studies. (2nd September 2014) - Cooper, R; Benzeval, M; Deary, IJ; Dennison, EM; Der, G; Gale, CR; Inskip, HM; Jagger, C; Kirkwood, TB; Lawlor, DA; Robinson, SM; Starr, JM; et al.
Abstract : Background: Epidemiological studies have shown that weaker grip strength in later life is associated with subsequent disability, morbidity and mortality. Grip strength is a key component of the sarcopenia and frailty phenotypes and yet it is unclear how individual measurements of grip strength should be interpreted in the clinical setting. Using data from general population studies conducted in Great Britain, our objective was to produce cross-sectional centile values for grip strength across the life course. Methods: We combined data from 12 general population studies conducted in Great Britain which had measured grip strength using a range of different dynamometers and measurement protocols. We produced centile curves using the Box-Cox Cole and Green distribution. We carried out a series of sensitivity analyses to assess the impact on the centiles produced of dynamometer type and measurement position (seated or standing). Results: We combined 60, 803 observations from 49, 964 participants (26, 687 female) to produce gender-stratified cross-sectional centile curves for grip strength from ages 4 to 90 years. The curves suggested three overall periods: an increase to peak in early adult life, maintenance through to midlife and decline from midlife onwards. Males were on average 1.7 times stronger than females from age 25 onwards: males' peak median grip was 51kg between ages 29 and 39, compared to 31kg in females between ages 26 and 42. Sensitivity analyses suggested our findings were robust to protocol differences between studies. Weak grip strength, defined as strength at least 2.5 SDs below the gender-specific peak mean, increased sharply with age, reaching a prevalence of 23% in males and 27% in females by age 80. Conclusion: This is the first study to provide normative data for grip strength across the life course. Our data were drawn from many studies which, in keeping with clinical practice, had used a variety of different measurement protocols; sensitivity analyses suggested that our centile curves were robust to these differences. These centile values have the potential to inform the clinical assessment of grip strength which is recognised as an important part of the identification of people with sarcopenia and frailty.